(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2017)
In order to suggest quinoa as a quality product with a Colombian seal, the objective of this study is to benchmark Colombian quinoa production/marketing against the production chains of Bolivia and Peru (world leaders in production and exports) through Porter’s competitiveness diamond. The conclusion is that Bolivia continues to be important but its productivity has limited its growth, as its production continues to depend on low labor costs. On the other hand, Peru’s growing development in the sector can serve as an example for Colombia.